Comparative analysis of the religions relation to the global problems of ecology and the place of Islam in the stable development of the society - K. M. Alilova; G. M. Abdurakhmanov; P. D. Alieva (Юг России: экология, развитие)
The main religions connecting the problems of ecology are analyzed. And also Islamic religion is characterized and its place in stable development of community.